Explore BrainMass

Explore BrainMass

    Expressing Roots of Quadratic Equations

    This content was COPIED from BrainMass.com - View the original, and get the already-completed solution here!

    If (x + 2)(x - 4) = 0 indicates that x + 2 = 0 or x - 4 = 0, explain why (x + 2)(x - 4) = 6 does not mean x + 2 = 6 or x - 4 = 6. Could we solve the equation using x + 2 = 3 and x - 4 = 2 because (3)(2) = 6?

    © BrainMass Inc. brainmass.com March 4, 2021, 7:37 pm ad1c9bdddf
    https://brainmass.com/math/algebra/expressing-roots-quadratic-equations-112158

    Solution Preview

    First let us understand why (x + 2)(x - 4) = 0 indicates that x + 2 = 0 or x - 4 = 0

    From the properties of numbers, we know that, any real number multiplied by zero results zero.
    i.e., a*0=0 for any real number a.
    Product of any two non zero numbers yields us a non ...

    Solution Summary

    The allowable expressions for roots of quadratic equations are explained. An equation is solved.

    $2.49

    ADVERTISEMENT